Perceived Appropriateness of Shared Decision‐making in the Emergency Department: A Survey Study. (22nd March 2016) - Probst, Marc A.; Kanzaria, Hemal K.; Frosch, Dominick L.; Hess, Erik P.; Winkel, Gary; Ngai, Ka Ming; Richardson, Lynne D.
Abstract: Objectives: The objective was to describe perceptions of practicing emergency physicians (EPs) regarding the appropriateness and medicolegal implications of using shared decision‐making (SDM) in the emergency department (ED). Methods: We conducted a cross‐sectional survey of EPs at a large, national professional meeting to assess perceived appropriateness of SDM for different categories of ED management (e.g., diagnostic testing, treatment, disposition) and in common clinical scenarios (e.g., low‐risk chest pain, syncope, minor head injury). A 21‐item survey instrument was iteratively developed through review by content experts, cognitive testing, and pilot testing. Descriptive and multivariate analyses were conducted. Results: We approached 737 EPs; 709 (96%) completed the survey. Two‐thirds (67.8%) of respondents were male; 51% practiced in an academic setting and 44% in the community. Of the seven management decision categories presented, SDM was reported to be most frequently appropriate for deciding on invasive procedures (71.5%), computed tomography (CT) scanning (56.7%), and post‐ED disposition (56.3%). Among the specific clinical scenarios, use of thrombolytics for acute ischemic stroke was felt to be most frequently appropriate for SDM (83.4%), followed by lumbar puncture to rule out subarachnoid hemorrhage (73.8%) and CT head for pediatric minor head injury (69.9%). Most EPs (66.8%) felt that using and documenting SDM would decrease their medicolegal risk while a minority (14.2%) felt that it would increase their risk. Conclusions: Acceptance of SDM among EPs appears to be strong across management categories (diagnostic testing, treatment, and disposition) and in a variety of clinical scenarios. SDM is perceived by most EPs to be medicolegally protective.